Financial Volatility Spillover in COVID-19 Pandemic Period: Evidence from the US and ASEAN Stock Market - Nurfaiz, Rifki; Chalid, Dony Abdul (Jurnal Keuangan dan Perbankan, 2022)
A recession is part of the economic cycle that occurs in a certain period. This article investigates the effects of volatility spillover in the COVID-19 pandemic that occurred in 2020 using stock market index data from the US and ASEAN countries: Indonesia, Malaysia, Singapore, Thailand, and the Philippines. Investigations in the prior, during, and post of the 2008 crisis period were also investigated to analyze the differences between the two. This study used the BEKK-MGARCH model to analyze the spillover effect of volatility between stock indices. The results are not much different from previous research from Vo (2020), where all ASEAN stock markets except the Philippines were affected by the volatility spillover by the US market. In general, from the two periods, each ASEAN index also gives a bidirectional influence of volatility to other ASEAN indices, with the JKSE, KLSE, and SET indices having the most volatility integrated with other indices and the PSE index being the least integrated.